Sistem Monitoring berbasis Desktop untuk Perangkat Mini Exhausting Pada Proses Pengalengan Ikan - Syamsiar Kautsar; Wahyu Suryaningsih; Abi Bakri; Budi Hariono; Aulia Brilliantina; Rizza Wijaya (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2022)
One of the potential marine resources that can develop the economy is fisheries. Fishery potential in Indonesia is estimated at 7.3 million tons per year. However, the community has only utilized the empowerment of fish potential so far, only 80%. Therefore we need a processing business that can extend the shelf life while increasing the added value of fishery products. One of the processing processes that can preserve longevity is the canning process. Canning can be interpreted as processing using a sterilization temperature that aims to save the food material from the spoilage process. In a previous study, mini exhausting equipment was developed to produce fish in cans with a capacity of 200 115mL cans. A temperature monitoring system is needed during the exhausting process to ensure quality. Therefore, in this study, a desktop application-based monitoring system was created to display and store temperature data during the exhausting process.